Phloem Sap Proteins Are Part of a Core Stress Responsive Proteome Involved in Drought Stress Adjustment - Castañeda, Veronica; González, Esther M.; Wienkoop, Stefanie (Frontiers in Plant Science, 2021)
During moderate drought stress, plants can adjust by changes in the protein profiles of the different organs. Plants transport and modulate extracellular stimuli local and systemically trough commonly induced inter- and intracellular reactions. However, most proteins are frequently considered, cell and organelle specific. Hence, while signalling molecules and peptides can travel systemically throughout the whole plant, it is not clear, whether protein isoforms may exist ubiquitously across organs, and what function those may have during drought regulation. By applying shotgun proteomics, we extracted a core proteome of 92 identical protein isoforms, shared ubiquitously amongst several Medicago truncatula tissues, including roots, phloem sap, petioles and leaves. We investigated their relative distribution across the different tissues and their response to moderate drought stress. In addition, we functionally compared this plant core stress responsive proteome with the organ-specific proteomes. Our study revealed plant ubiquitous protein isoforms, mainly related to redox homeostasis and signalling and involved in protein interaction networks across the whole plant. Furthermore, about 90% of these identified core protein isoforms were significantly involved in drought stress response, indicating a crucial role of the Core Stress Responsive Proteome (CSRP) in the plant organ cross-communication, important for a long-distance stress-responsive network. Besides, the data allowed for a comprehensive characterization of the phloem proteome, revealing new insights into its function. For instance, CSRP protein levels involved in stress and redox are relatively more abundant in the phloem compared to the other tissues already under control conditions. This suggests a major role of the phloem in stress protection and antioxidant activity enabling the plants metabolic maintenance and rapid response upon moderate stress. We anticipate our study to be a starting point for future investigations of the role of the core plant proteome. Under an evolutionary perspective, CSRP would enable communication of different cells with each other and the environment being crucial for coordinated stress response of multicellular organisms.